A Study on Customer Satisfaction of Hero Honda Motor Cycle in Coimbatore, Tamil Nadu - Vennila, A. (Indian Journal of Finance, 2011)
This study was carried out for a period of one month. The main objective of the study is to identify the customer satisfaction on Hero Honda motorcycles in Coimbatore, Tamil Nadu. The objectives also include, evaluating the opinion of the customers about their preference, and the parameters to improve the features of Hero Honda motorcycle.